2011
DOI: 10.1890/es11-00097.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term warming on low and high latitude forest ant communities

Abstract: Abstract. Climatic change is expected to have differential effects on ecological communities in different geographic areas. However, few studies have experimentally demonstrated the effects of warming on communities simultaneously at different locales. We manipulated air temperature with in situ passive warming and cooling chambers and quantified effects of temperature on ant abundance, diversity, and foraging activities (predation, scavenging, seed dispersal, nectivory, granivory) in two deciduous forests at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 46 publications
9
49
4
Order By: Relevance
“…For instance, if Crematogaster lineolata benefits from warming by increasing foraging, evenness of the assemblage could be reduced by competitive displacement [44]; such results have also been observed for plant assemblages [48]. Effects of warming on species interactions have been demonstrated in a variety of aquatic and terrestrial systems [49], [50] including plant-herbivore [51], host-parasitoid [52], and trophic interactions [14], [53][56], ultimately influencing the composition of communities.…”
Section: Discussionmentioning
confidence: 87%
“…For instance, if Crematogaster lineolata benefits from warming by increasing foraging, evenness of the assemblage could be reduced by competitive displacement [44]; such results have also been observed for plant assemblages [48]. Effects of warming on species interactions have been demonstrated in a variety of aquatic and terrestrial systems [49], [50] including plant-herbivore [51], host-parasitoid [52], and trophic interactions [14], [53][56], ultimately influencing the composition of communities.…”
Section: Discussionmentioning
confidence: 87%
“…One exception is a long‐term forest warming experiment at two sites located near the endpoints of the latitudinal transect we sampled (Pelini et al ., ). Work in this system has focused on ants and has consistently found striking and heterogeneous effects of warming on community composition and species abundances at the midlatitude site, and weaker effects at the high‐latitude site (Pelini et al ., , ; Diamond et al ., ; Stuble et al ., ). These results are similar to ours and support the pattern of midlatitude heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that air temperature can potentially influence ant community structure (Arnan et al 2007, Wittman et al 2010, Lessard et al 2011, diversity (Kaspari et al 2000, Sanders et al 2007, Pelini et al 2011a), colony survival , worker density (Pelini et al 2011a, Diamond et al 2012a, foraging behavior (Ruano et al 2000, Pelini et al 2011a, Stuble et al 2013, and competitive interactions (Cerda et al 1997(Cerda et al , 1998.…”
Section: Methodsmentioning
confidence: 99%